2009
DOI: 10.1177/104063870902100401
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Criteria to Confirm White-nose Syndrome in Bats

Abstract: White-nose syndrome (WNS) is a cutaneous fungal disease of hibernating bats associated with a novel Geomyces sp. fungus. Currently, confirmation of WNS requires histopathologic examination. Invasion of living tissue distinguishes this fungal infection from those caused by conventional transmissible dermatophytes. Although fungal hyphae penetrate the connective tissue of glabrous skin and muzzle, there is typically no cellular inflammatory response in hibernating bats. Preferred tissue samples to diagnose this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
329
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(344 citation statements)
references
References 3 publications
8
329
2
Order By: Relevance
“…destructans (formerly known as Geomyces destructans ) is a psychrophilic fungus that causes white-nose syndrome (WNS) of hibernating and cave-roosting bats, a fatal disease that has devastated bat populations in parts of the United States and Canada. A visually conspicuous white fungus grows on the face, ears or wings of stricken bats; infiltration of the hyphae into membranes and tissues leads to severe damage (Meteyer et al 2009). Bats that exhibit WNS have little or no fat reserves, which are essential for their survival throughout and after hibernation (Blehert et al 2009).…”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…destructans (formerly known as Geomyces destructans ) is a psychrophilic fungus that causes white-nose syndrome (WNS) of hibernating and cave-roosting bats, a fatal disease that has devastated bat populations in parts of the United States and Canada. A visually conspicuous white fungus grows on the face, ears or wings of stricken bats; infiltration of the hyphae into membranes and tissues leads to severe damage (Meteyer et al 2009). Bats that exhibit WNS have little or no fat reserves, which are essential for their survival throughout and after hibernation (Blehert et al 2009).…”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…White-nose syndrome is characterized by the presence of profuse but delicate hyphae and conidia produced by the fungus on the muzzles, wing membranes, and pinnae of infected hibernating bats; the fungal hyphae pervade the living skin tissues of infected bats, with hair follicles and sebaceous glands being effaced Meteyer et al, 2009). Severe wing damage associated with fungal invasion may be seen in bats that have recently emerged from hibernation (Meteyer et al, 2009;Cryan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies indicated that the cottony appearance was due to fungal growth. The extensive fungal colonization of bat skin and hair, characteristic histopathological appearance, and exclusive presence of a specific fungal DNA in the animals' tissues led to the discovery of the causal agent-a newly described species called Geomyces destructans [2][3][4][5][6]. Subsequent studies revealed that this condition has caused the deaths of nearly a million bats in the Northeast and it has rapidly spread to other parts of the country [7].…”
mentioning
confidence: 99%
“…Bats afflicted with WNS have many symptoms, such as, emaciation, epidermal erosion and ulcers, and extensive wing damage [4,10]. Accordingly, this disease can be confirmed by the morphological appearance of the fungus on any part of the body, histopathology of affected tissues with demonstration of hyphae-conidia, or demonstration of G. destructans by PCR-nucleotide sequencing [3,4,6,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation